Religious Moderation In Classical and Contemporary Islamic Thought: A Comparative Study Of Ulama Perspectives - Ani Maghfiroh; Selvi Ratna Sari; Zuhdiyah; Maryamah (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2026)
Religious Religious moderation (wasathiyyah) has emerged as a critical discourse in responding to the challenges of globalization, religious extremism, and increasing social polarization. Although the concept has deep roots in classical Islamic scholarship, its contemporary interpretation has evolved to address modern social realities. This study aims to analyze the concept of religious moderation from the perspectives of classical and contemporary Muslim scholars, identify their similarities and differences, and examine its relevance to contemporary society. The research employs a qualitative descriptive-comparative approach through library research and qualitative content analysis of classical and contemporary Islamic literature. The collected data were analyzed using thematic analysis to identify major patterns and conceptual relationships. The findings reveal that both classical and contemporary scholars share the same normative foundations of religious moderation, namely balance (tawazun), justice ('adl), wisdom (hikmah), and public welfare (maslahah). However, classical scholars primarily emphasize moderation as a moral and spiritual principle, while contemporary scholars expand its application to issues of pluralism, democracy, social cohesion, and the prevention of religious extremism. The study further demonstrates that contemporary interpretations of wasathiyyah represent a contextual adaptation rather than a departure from classical Islamic thought. By integrating these two perspectives, this research proposes a comprehensive framework of religious moderation that combines theological authenticity with social relevance. The findings contribute to the development of Islamic studies and provide practical implications for strengthening moderation through education, religious leadership, and public policy in multicultural societies.